Uji Aktivitas Antijamur Fraksi Etanol Rimpang Temu Kunci (Boesenbergia pandurata (Roxb.) Schlecht) Terhadap Candida albicans dan Trichophyton mentagrophytes Beserta Profil Kromatografi Lapis Tipisnya - Saryanti , Dwi (Jurnal Farmasi (Journal of Pharmacy), 2012)
In Indonesia, skin and nail diseases due to fungal infection is still prevalent, especially because the air is humid and hot, less of the In Indonesia, skin and nail diseases due to fungal infection is still prevalent, especially because the air is humid and hot, less of the levels of health and poor environmental sanitation. Among the diseases caused by Candida albicans and Trichophyton mentagrophytes. On the other hand some plants from the Zingiberaceae, among the plants temu ireng, turmeric, temu giring, and temu lawak has been demonstrated to have antifungal activity by previous researchers. Temu kunci is one of the plants from the Zingberaceae, for it has done the research activities of temu kunci ethanol fraction (Boesenbergia pandurata (Roxb.) Schlecht) of the fungus Candida albicans and Trichophyton mentagrophytes. Antifungal activity assays performed with solid dilution method. The results showed that Minimal Bacterisid Concentration (MBC) of the temu kunci ethanol fraction to the growth of the fungus Candida albicans and Trichophyton mentagrophytes are the same is 4%. Thin Layer Chromatography test for examining the content of the compound in plants using a mobile phase of ethyl acetate: benzene petroletum (9:11) with vanillin spray reagent-phase sulfuric acid and ethyl acetate: methanol: water (100:13,5:10) with reagents sitroborat spray and NH3 vapor. Profile kromatrogram temu kunci ethanol fractions showed that fractions containing compounds group terpenoids and flavonoids.